Mini review: karyotypic survey in triatominae subfamily (Hemiptera, Heteroptera) - Alevi, Kaio Cesar Chaboli [UNESP]; Rosa, Joao Aristeu da [UNESP]; Oliveira, Maria Tercilia Vilela de Azeredo [UNESP] (OMICS International, 2013)
The Triatominae subfamily consists of 145 species distributed in 18 genera and grouped in six tribes. Currently, there are 86 karyotypes described in the literature, distributed in 11 genera. There are five chromosomal complements described for these bloodsucking insects, out more, 22 (20A+XY), 23 (20A+X1X2Y), 24 (20A+X1X2X3Y), 21 (18A+X1X2Y), 25 (22A+X1X2Y). Thus, we review all triatomine species with the number of chromosomes described in the literature. Through these data highlight the importance of further analysis cytogenetic with karyotype description in Triatominae subfamily, since it can help as an important tool cytotaxonomy and mainly allows the understanding of the evolution of this important group of insect vectors of Chagas disease.
Keywords: Karyotype; Holocentric chromosome; Diploid chromosome set